Anti-inflammatory approaches to ischaemic stroke prevention - Kelly, Peter J; Murphy, Sean; Coveney, Sarah; Purroy, Francisco; Lemmens, Robin; Tsivgoulis, Georgios; Price, Chris (Journal of neurology, neurosurgery and psychiatry, 2018)
Stroke is a major cause of neurological morbidity and mortality. Atherosclerosis is a major contributor to first and recurrent stroke. A growing evidence base indicates that inflammation is a key process in the pathogenesis of atherosclerosis, leading to thromboembolic events. In this review, we summarise the evidence linking inflammation to stroke risk and discuss clinical trials addressing the ’inflammation hypothesis' in coronary disease and stroke. Trial registration number CONVINCE trial ClinicalTrials.gov number; NCT 02898610; Pre-results.